The Influence of Compensation, Work Facilities and Work Discipline on Employee Performance at CV. Aufco Bandung - Pujihandayani, Dinda Ilhan; Gumilar, Dedi (Dinasti Publisher, 2023)
The purpose of this study was to determine the effect of compensation, work facilities, and work discipline on employee performance at CV. Aufco Bandung both partially and simultaneously. The population in this study were all employees at CV. Aufco Bandung, totaling 32 employees. The sampling technique used in this study was saturated sampling technique. The method used in this research is Quantitative Method with data collection techniques used are interviews and distributing questionnaires to respondents. The data analysis technique used is multiple linear regression with the SPSS program. The results of the study concluded that: (1) compensation has a significant effect on employee performance. (2) work facilities have a significant effect on employee performance. (3) work discipline has a significant effect on employee performance. In simultaneous testing, compensation, work facilities, and work discipline have a positive and significant effect on employee performance at CV. Aufco Bandung. The magnitude of the influence of compensation, work facilities, and work discipline is indicated by the Adjusted R Square value of 67.8% and the remaining 32.2% is influenced by other variables not examined in this study.